1977
DOI: 10.1113/jphysiol.1977.sp011943
|View full text |Cite
|
Sign up to set email alerts
|

A potassium contribution to the response of the barnacle photoreceptor.

Abstract: SUMMARY1. Intracellular recording from photoreceptors in the lateral eye of the barnacle show a brief negative-going 'dip' shortly after the onset of the late receptor potential. This phase can sometimes result in a hyperpolarization relative to the resting membrane potential.2. The dip is prominent in light-adapted cells and is reduced by darkadaptation. Low extracellular Ca2+ also reduces it.3. The amplitude of the dip changes inversely with the K+ concentration in the saline.4. The amplitude of the dip depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…In this regard it is of some interest that quinine and related drugs, which block the effects of ATP in many tissues (Burnstock, 1972) also specifically uncouple increases of intracellular calcium levels from the activation of the (calcium-dependent) potassium channels (ArmandoHardy, Ellory, Ferreira, Fleminger & Lew, 1975; B.J.P. 70/3-F Hanani & Shaw, 1977). It is therefore feasible that the release or local mobilization of a purine derivative such as ATP could form the link between intracellular calcium levels and potassium channels.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard it is of some interest that quinine and related drugs, which block the effects of ATP in many tissues (Burnstock, 1972) also specifically uncouple increases of intracellular calcium levels from the activation of the (calcium-dependent) potassium channels (ArmandoHardy, Ellory, Ferreira, Fleminger & Lew, 1975; B.J.P. 70/3-F Hanani & Shaw, 1977). It is therefore feasible that the release or local mobilization of a purine derivative such as ATP could form the link between intracellular calcium levels and potassium channels.…”
Section: Discussionmentioning
confidence: 99%
“…l b in Burgess et al 1979). Rather large concentrations of quinine were needed, blockade of K loss induced by A23187 being complete at 1 mm and half-maximal at Lew & Ferreira (1978) and Hanani & Shaw (1977) respectively. Similar experiments were carried out with apamin.…”
Section: Inhibitory Effects Of Quinine and Apaminmentioning
confidence: 99%
“…In the present work this effect on K movement has been shown to occur in guinea-pig hepatocytes, and the underlying changes in Ca flux initiated by A23187 and several other agents have been examined. In addition, it has been found that the movements of K triggered by a rise in Ca are abolished by quinine, as in erythrocytes (Armando-Hardy, Ellory, Ferreira, Fleminger & Lew, 1975), barnacle photoreceptors (Hanani & Shaw, 1977) and pancreatic islet cells (Atwater, Dawson, Ribalet & Rojas, 1979). We have also observed that a bee venom neurotoxin, apamin (Habermann & Reiz, 1965;Callewaert, Shipolini & Vernon, 1968;Habermann, 1972), produces a similar uncoupling in hepatocytes though not in red cells and ghosts.…”
Section: Introductionmentioning
confidence: 99%
“…There is abundant evidence, however, particularly at high light intensities and during prolonged illumination, that non-light dependent changes in membrane permeability occur which modify the shape of the receptor potential. These secondary effects result mostly from the activation of voltage-dependent permeabilities in the membrane (Naka & Eguchi, 1962;Baumann, 1968; Baylor, Hodgkin & Lamb, 1974; Werblin, 1975;Hanani & Shaw, 1977;Pepose & Lisman, 1978;Fain, Quandt & Gerschenfeld, 1977). Because these secondary changes in membrane potential form part of the signal conveyed by the receptor about light it is important to separate clearly light dependent from non-light dependent changes in permeability.…”
Section: Introductionmentioning
confidence: 99%